Type 2 myocardial infarction in a patient with acute abdomen due to an incarcerated Amyand's Hernia. (2020) - Cabrera, Paulo; Roman, Carlos; Barbosa, Silvia; Alvarado, Fabian; Diaz, Esteban; Martinez, Mayerlin
Highlights: The type 2 myocardial infarction is an imbalance in the supply of oxygen to myocardium not related by an atherothrombotic disease which can be caused by an acute abdomen. The Amyand's Hernia with an myocardial ischemic pathology is notoriously uncommon in the surgical setting being of high mortality for the patient. Although the holistic approach of patients with acute abdomen is the work of the surgeon, is important the fact of knowing the different patterns of clinical presentation of pathologies that not corresponding to the surgical specialty. Abstract: Background: Type 2 myocardial infarction (MIT2) is characterized by higher mortality rates compared to conventional type 1 infarction according to the European Society of Cardiology (ESC) in 2018. The purpose of this case is to identify appropriate therapeutic measures. A case of an Amyand's Hernia that produced an MIT2 is described in this work. Case report: A 77-year-old male was admitted to our emergency department for acute abdominal pain in the right lower quadrant associated with the presence of an ipsilateral inguinal hernia with signs of peritoneal irritation, while complaining of chest pain. A positive troponin indicated the presence of myocardial infarction. A laparotomy was performed with the finding of an incarcerated right inguino-scrotal hernia that contained the gangrenous and perforated cecal appendix (Amyand hernia type 3). The treatment consisted of surgical correction of the hernia, an appendectomy, antibiotics and support in the intensive care unit with a positive outcome. The diagnosis of Amyand hernia type 3 was established intraoperatively, and by imaging, confirming the presence of an MIT2 according to the criteria of the fourth definition of ECS infarction. Conclusion: In the surgical environment it is strange to find patients who present with acute abdominal pain and a myocardial infarction at the same time. It is necessary for the consultant to recognize these two entities to make a correct diagnosis and provide timely treatment to reduce any possibility of patient mortality.